Perhitungan Cadangan Premi Asuransi Jiwa Dwiguna Menggunakan Metode Premium Sufficiency dengan Asumsi Usia Pecahan - Rafli Ramadhan; Fuji Lestari (Research and Community Service UNIVERSITAS KALBIS, 2025)
Risk is a part of human life that can cause financial losses, so insurance is needed to deal with these risks. Insurance is an agreement between an insurance company and a policyholder, with the company required to provide compensation for financial losses experienced by the policyholder. As an imbalance, the policyholder needs to pay a certain amount of premium. This study aims to analyze the calculation of premium reserves using the Premium Sufficiency method with the assumption of fractional age. The Premium Sufficiency method is one of the prospective premium reserve calculations using gross premiums. In reality, insurance participants do not always register at an integer age, but at a fractional age, so a fractional age assumption is needed. The results of the premium reserve calculation using Premium Sufficiency for the fractional age assumption increase every year, with the premium reserve value at the end of the insurance period increasing the same as the amount of insurance. In addition, the difference in the premium reserve value between the case of a premium payment period of 5 years and 10 years in the first year for the fractional age assumption is Rp 21,498,124,302.